Innovation-Based Business Education Strategies to Foster Community Engagement in Local Economic Development - Sudirjo, Frans; Novianti, Rini; Santosa, Sonny (PT. LITERASI SAINS NUSANTARA, 2024)
Business education plays a crucial role in shaping human resources with skills and knowledge relevant to local economic needs. However, conventional approaches in business education may not fully meet market demands and latest innovations. This research aims to identify and formulate innovation-based business education strategies that can effectively foster community engagement in local economic development. This research method employs a literature review with a qualitative approach focused on contributions to community service. Descriptive analysis will be used to depict findings from 27 selected articles retrieved from Google Scholar within the timeframe of 2001-2023. The study findings indicate that innovation-based business education is a primary key to strengthening community engagement in local economic development in the current dynamic era. These strategies emphasize the integration of technology into the curriculum, collaboration among universities, industries, and government, practical learning, the development of social awareness and business responsibility, direct community involvement in the teaching-learning process, stimulation of creativity and entrepreneurship, integration with community development programs, as well as interdisciplinary approaches to problem-solving.